An acquired factor V inhibitor induced uncontrolled bleeding in a postsurgery patient. Issue 1 (1st December 2020) - Bruna, Riccardo; Moia, Riccardo; Valpreda, Alessandra; Dosio, Enrico; Rolla, Roberta; Federici, Augusto; Dianzani, Umberto; Gaidano, Gianluca; Patriarca, Andrea
Abstract: This case report highlights the challenges in controlling bleeding and correcting coagulation tests through the use of bypassing agents in patients with FV inhibitors. Abstract : This case report highlights the challenges in controlling bleeding and correcting coagulation tests through the use of bypassing agents in patients with FV inhibitors.